Use of organic acids to reduce Salmonella Typhimurium excretion in swine - da Silva, Daniela Gomes [UNESP]; de Oliveira Moura, Eduarda Alexandra Gonçalves [UNESP]; Sanches, Thainara Vitoria Carnevalli [UNESP]; Turco, Caio Henrique [UNESP]; Zambotti, Beatriz Belloni [UNESP]; Petri, Fernando Antônio Moreira [UNESP]; Storino, Gabriel Yuri [UNESP]; de Souza Almeida, Henrique Meiroz [UNESP]; Rabelo, Isabela Peixoto [UNESP]; Mechler-Dreibi, Marina Lopes [UNESP]; Sonalio, Karina [UNESP]; Ravetti, Renato; et al. (My University, 2023)
The use of antimicrobials as growth promoters and disease prevention is being constantly reduced in several animal production systems, including in the swine industry. Therefore, this study aimed to evaluate the effectiveness of using acidifiers to control Salmonella Typhimurium in 65-day-old pigs by detecting the pathogen in organs at euthanasia. For this, 24 piglets were divided into two experimental groups consisting of 12 piglets each. An untreated control group (G1) and a treatment group (G2) received a liquid organic acidifier in the drinking water for 10 days (D-5 to D5). Five days after the start of treatment (D0), all piglets were challenged with 106 CFU of Salmonella Typhimurium and assessed for 12 days (D12). Every three days (D3, D6, D9, and D12), three animals from each experimental group were euthanized and then submitted for necropsy. Samples from the intestines (ileum, cecum, mesenteric lymph nodes, and ileocolic lymph nodes), liver, spleen, and lungs were collected to isolate Salmonella. The results show that, numerically, Salmonella isolation in the organs of G2 was lower than in G1 and that the number of positive cecum samples in G1 (66.7%; 8/12) was statistically different from the number of positive models in G2 (16.7%; 2/12), with a reduction of 28.6% of the total cecum positive samples in the treated group compared to the control. Therefore, it was observed that the liquid organic acidifier product could reduce the colonization of organs by Salmonella Typhimurium.
Uso de ácidos orgânicos para reduzir a excreção de Salmonella Typhimurium em suínos
Keywords: Euthanasia; Excretion; Organic acids; Salmonella Typhimurium; Swine